Catalysis of linear alkene metathesis by Grubbs-type ruthenium alkylidene complexes containing hemilabile α,α-diphenyl-(monosubstituted-pyridin-2-yl)methanolato ligands - Tole, Tegene T.; Jordaan, Johan H. L.; Vosloo, Hermanus C. M. (Beilstein Journal of Organic Chemistry, 2019)
Four new Grubbs-type precatalysts [RuCl(H2IMes)(O^N)(=CHPh)], where [O^N = α,α-diphenyl-(3-methylpyridin-2-yl)methanolato, α,α-diphenyl-(4-methylpyridin-2-yl)methanolato, α,α-diphenyl-(5-methylpyridin-2-yl)methanolato and α,α-diphenyl-(3-methoxypyridin-2-yl)methanolato] were synthesized and tested for their activity, stability and selectivity in the 1-octene metathesis reaction. Overall the precatalysts showed good activity and high stability for the metathesis of 1-octene at temperatures above 80 °C and up to 110 °C. Selectivities towards the primary metathesis products, i.e., 7-tetradecene and ethene, above 85% were obtained with all the precatalysts at 80 and 90 °C. High selectivities were also observed at 100 °C for the 4-Me- and 3-OMe-substituted precatalysts. With an increase in temperature an increase in isomerisation products and secondary metathesis products were observed with the latter reaching values >20% for the 3-OMe- and 3-Me-substituted precatalysts at 110 and 100 °C, respectively. All the precatalysts exhibits first-order kinetics at 80 °C with the 3-substituted precatalysts the slowest. The behaviour of the 3-substituted precatalysts can be attributed to electronic and steric effects associated with the adjacent bulky phenyl groups.
Keywords: Grubbs-type precatalyst; hemilabile; 1-octene metathesis; pyridinyl-alcoholato ligand

Handbook of Metathesis - Grubbs, R. H.; Wenzel, A. G.; O'Leary, D. J.; Khosravi, E. (Wiley-VCH Verlag GmbH, 2015)

Olefin Metathesis: Theory and Practice - Grela, K. (Wiley-VCH, 2014)

(untitled) - Slugovc, C.; Burtscher, D.; Stelzer, F.; Mereiter, K. (Organometallics, 2005)

(untitled) - Monsaert, S.; Vila, A. L.; Drozdzak, R.; Van Der Voort, P.; Verpoort, F. (Chem. Soc. Rev., 2009)

(untitled) - Tole, T.; Jordaan, J.; Vosloo, H. (Molecules, 2018)

(untitled) - van der Schaaf, P. A.; Abbenhuis, R. A. T. M.; Grove, D. M.; Smeets, W. J. J.; Spek, A. L.; van Koten, G. (J. Chem. Soc., Chem. Commun., 1993)

U.S. Patent - Van Der Schaaf, P. A.; Mühlebach, A.; Hafner, A.; Kolly, R. (Heterocyclyl ligand containing ruthenium and osmium catalysts, 2002)

(untitled) - Wijkens, P.; Jastrzebski, J. T. B. H.; van der Schaaf, P. A.; Kolly, R.; Hafner, A.; van Koten, G. (Org. Lett., 2000)

(untitled) - Denk, K.; Fridgen, J.; Herrmann, W. A. (Adv. Synth. Catal., 2002)

(untitled) - Jordaan, M.; Vosloo, H. C. M. (Adv. Synth. Catal., 2007)

(untitled) - van der Gryp, P.; Barnard, A.; Cronje, J.-P.; de Vlieger, D.; Marx, S.; Vosloo, H. C. M. (J. Membr. Sci., 2010)

(untitled) - du Toit, J. I.; Jordaan, M.; Huijsmans, C. A. A.; Jordaan, J. H. L.; van Sittert, C. G. C. E.; Vosloo, H. C. M. (Molecules, 2014)

(untitled) - du Toit, J. I.; van der Gryp, P.; Loock, M. M.; Tole, T. T.; Marx, S.; Jordaan, J. H. L.; Vosloo, H. C. M. (Catal. Today, 2016)

(untitled) - Tole, T. T.; du Toit, J. I.; van Sittert, C. G. C. E.; Jordaan, J. H. L.; Vosloo, H. C. M. (Catalysts, 2017)

WIPO/PCT Patent - Slugovc, C.; Wappel, J. (Olefin Metathesis, 2013)

(untitled) - Schachner, J. A.; Cabrera, J.; Padilla, R.; Fischer, C.; van der Schaaf, P. A.; Pretot, R.; Rominger, F.; Limbach, M. (ACS Catal., 2011)

(untitled) - Cabrera, J.; Padilla, R.; Bru, M.; Lindner, R.; Kageyama, T.; Wilckens, K.; Balof, S. L.; Schanz, H.-J.; Dehn, R.; Teles, J. H.; Deuerlein, S.; Müller, K.; et al. (Chem. – Eur. J., 2012)

(untitled) - Cabrera, J.; Padilla, R.; Dehn, R.; Deuerlein, S.; Gułajski, Ł.; Chomiszczak, E.; Teles, J. H.; Limbach, M.; Grela, K. (Adv. Synth. Catal., 2012)

(untitled) - Getty, K.; Delgado-Jaime, M. U.; Kennepohl, P. (J. Am. Chem. Soc., 2007)

(untitled) - Ritter, T.; Hejl, A.; Wenzel, A. G.; Funk, T. W.; Grubbs, R. H. (Organometallics, 2006)

(untitled) - Ulman, M.; Grubbs, R. H. (Organometallics, 1998)

(untitled) - Jordaan, M.; van Helden, P.; van Sittert, C. G. C. E.; Vosloo, H. C. M. (J. Mol. Catal. A: Chem., 2006)

(untitled) - Herrmann, W. A.; Lobmaier, G. M.; Priermeier, T.; Mattner, M. R.; Scharbert, B. (J. Mol. Catal. A: Chem., 1997)